One hundredth anniversary of the Russian revolutions of 1917 (second article) - Antonovich, Ivan I. (Journal of the Belarusian State University. Sociology, 2019)
It is the authors intention to prove that Lenins revolutionary heritage was usurped and squandered by the people who stayed at the apex of political power, but whose personal interests of keeping it outweihged 5 the tasks of the defense of the goals of the revolution. It is the authors conviction that Stalin gained the upper hand over Trotsky when he put forward the idea of the victory of socialism. It was supported by the majority of the members of the bolshevik party members because the idea of the continuation of the world revolution, that was the aim of trotskists was rejected by the population exhausted by the civil war and the revolutionary that social and historical damage upheavals. It is the authors conclusion that social and historical damage having penetrated social system and consciousness, has not been overcome and that had tragic consequences which resulted in the tragic fate of the perestroika and preordained the end of the greatest historical experiment to create the social justice society.